Penguatan Manajemen Melalui Kepatuhan Pelaksanaan Perpajakan - Subadriyah Subadriyah; Jumaiyah Jumaiyah; Mahmudatus Sa'diyah (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This program of devotion is carried out at the Lembaga Studi Ekonomi dan Kebijakan Publik (LSEKP). This partner is located in the Village of East Jambu RT 08 RW 02, District Mlonggo Jepara. Mitra is a mobile community organization engaged in training activities and discussions to oversee public policy in Jepara.The purpose of science and technology is focused on providing the required tax training by partners. Method of implementing devotion using training and mentoring methods. Training is carried out to all management and members of the institution so that all know the obligation of the implementation of taxation properly. While assistance is given to the chairman of the institution and one member who takes care of administration and taxation. Assistance is done when calculating, preparing, paying and reporting tax obligations.The result of this service activity is: (1) partners are able to calculate, compile, pay and report their tax obligations correctly, (2) partners know sanctions and tax penalties, (3) partners obedient in carrying out tax obligations that is by paying and reporting on time Keywords: Management, Training and Assistance, Obedient Tax.